2021
DOI: 10.3389/fimmu.2021.697083
|View full text |Cite|
|
Sign up to set email alerts
|

Long Non-Coding RNAs in the Tumor Immune Microenvironment: Biological Properties and Therapeutic Potential

Abstract: Cancer immunotherapy (CIT) is considered a revolutionary advance in the fight against cancer. The complexity of the immune microenvironment determines the success or failure of CIT. Long non-coding RNA (lncRNA) is an extremely versatile molecule that can interact with RNA, DNA, or proteins to promote or inhibit the expression of protein-coding genes. LncRNAs are expressed in many different types of immune cells and regulate both innate and adaptive immunity. Recent studies have shown that the discovery of lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 167 publications
2
22
0
Order By: Relevance
“…Another example includes GAS5, which regulates the killing effect of NK cells and requires NK-dependent antitumor function [ 132 ]. At the TME level, lncRNAs are involved in controlling interaction between immune cells and tumor cells and induce the immunosuppressive microenvironment [ 133 ]. For instance, the upregulation of lnc-TIM3 in tumor-infiltrating CD8 + T cells prevents IFN-γ and IL-2 production and leads to T cell exhaustion in the TME [ 134 ].…”
Section: Targeting Time Using Rna-based Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example includes GAS5, which regulates the killing effect of NK cells and requires NK-dependent antitumor function [ 132 ]. At the TME level, lncRNAs are involved in controlling interaction between immune cells and tumor cells and induce the immunosuppressive microenvironment [ 133 ]. For instance, the upregulation of lnc-TIM3 in tumor-infiltrating CD8 + T cells prevents IFN-γ and IL-2 production and leads to T cell exhaustion in the TME [ 134 ].…”
Section: Targeting Time Using Rna-based Platformsmentioning
confidence: 99%
“…Additionally, studies have shown that lnc-DC plays an important role in DC differentiation and stimulates T cell activation during tumor immune response [ 137 ]. These reports are restricted to preclinical and clinical applications of lncRNA-mediated cancer immunotherapy [ 133 ]. LncRNAs that regulate the pivotal molecules and pathways during cancer progression are targeted in anticancer therapies, such as therapeutic vaccines, T cell-based treatments, and ICB.…”
Section: Targeting Time Using Rna-based Platformsmentioning
confidence: 99%
“…Moreover, in this Research Topic, increasing evidence indicates the role of non-coding RNA, including long non-coding RNAs (lncRNAs), in the immunomodulation of the TME ( 43 ). Hu et al.…”
Section: Cancer Intrinsic Epigenetic Mechanismsmentioning
confidence: 99%
“…T-UCRs, CCAT1, and many other lncRNAs have also been found to be linked to the development of CC [ 25 27 ]. In addition, lncRNAs are related to immune cells and the tumour immune microenvironment [ 28 , 29 ]. Tumour immunity is thought to have a significant influence on tumour development [ 30 ].…”
Section: Introductionmentioning
confidence: 99%